ANALISIS PENGARUH RASIO KEUANGAN DAN FAKTOR NON KEUANGAN TERHADAP PENERIMAAN OPINI AUDIT GOING CONCERN (Studi Empiris Pada Perusahaan Manufaktur di BEI tahun 2008-2010) - Muttaqin, Ariffandita Nuri; Sudarno, Sudarno (JURNAL AKUNTANSI DAN AUDITING, 2011)
This research was aimed to analyze and to obtain empirical evidences on the relationship betweenfinancial ratios (liquidity, profitability, activity, leverage, sales growth, market value) and nonfinancial factors (company size, public accountant reputation, previous audit report, auditorclienttenure,opinion shopping, audit lag) that affecting auditor’s decision to give a goingconcern audit opinion. The population in this research is manufacturing companies listed atIndonesian stock exchange from 2008-2010, the sampling was conducted by purposive samplingmethod, by criteria of the samples are companies had negative net income after tax at least twoperiod of financial statement. The results indicate that profitabilty, market value, previous auditreport, audit client tenure and opinion shopping are significantly affect the acceptence of goingconcern audit opinion. On the other hand, liquidity, activity, leverage, sales growth, companiessize, public accountant reputation, audit lag does not have affect on the acceptence of goingconcern audit opinion.